Evaluasi dan Perancangan Pengalaman Pengguna pada Aplikasi Adopsi Hewan Peliharaan menggunakan Metode Pengujian User Experience Questionnaire, Usability Testing dan Metode Perancangan User-Centered Design - Ghozi Akbar Wicaksono; Komang Candra Brata; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Adopsi is an application developed by PT. Oniyon Creative Revolution with the goal to make pet adoption process easier and simplified. Based on the evaluation conducted using user experience questionnaire (UEQ), the benchmark value was found to be at poor level. Besides of running well functionally, a system must consider improving their user experience in the hope of improving the ease when running the system. This study uses user-centered design approach by identifying the characteristics of users and involving users as respondents in the user experiences design process. The initial evaluation was performed on the existing design of application using UEQ method to determine the level of user experience according to respondent's impression, the usability testing method to find usability problems faced by respondents when doing the given task and open interview to collect user's problems and needs. There are 19 issues found and recommendations for solutions are made by following the design guidelines from 10 Usability Heuristics and Material design. The results of design process are implemented on a prototype as a test tool of design solution. Then evaluation of solution design performed using the same method as on the existing application design and improvements are made to get a final design that fits the user's needs.